Strategies to avoid salinity and hydric stress of pepper grafted plants - Penella, Consuelo; Nebauer, Sergio G.; San Bautista, Alberto; López-Galarza, Salvador (Elsevier, 2020)
Sweet pepper is one of the most important vegetable crops in arid and semiarid regions. Grafting has been proposed as an interesting strategy that improves the responses of crops under the salinity and hydric deficits occurring in these areas.